2020
DOI: 10.18099/ijetv.v6i02.1
|View full text |Cite
|
Sign up to set email alerts
|

Forensic Nursing in Humanitarian Forensics

Abstract: Humanitarian forensics has been established as a new entity, and it is bound to develop as a robust branch of science. It is a multidisciplinary subject with the involvement of experts from different fields of science. Forensic nursing too is an upcoming branch of nursing science and is a relatively new discipline of science. Forensic nursing science is expanding in various countries. This paper will describe and discuss the various important aspects of Humanitarian forensics and forensic nurses' utility in hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…With regard to language, 24 were published in English ( 38 ) . As for the location, 20 publications were ­produced in the United States of America (USA) ( 17 33 , 35 , 40 , 44 ) , three in Brazil ( 36 , 42 , 43 ) , three in India ( 34 , 39 41 ) and two in Japan ( 37 , 38 ) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to language, 24 were published in English ( 38 ) . As for the location, 20 publications were ­produced in the United States of America (USA) ( 17 33 , 35 , 40 , 44 ) , three in Brazil ( 36 , 42 , 43 ) , three in India ( 34 , 39 41 ) and two in Japan ( 37 , 38 ) .…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the origin of the disaster, it was identified that a publication occurred after the Oklahoma attack in 1995 ( 17 ) , four after the September 11, 2001 attacks ( 22 ) ; tsunami in India, in 2004 ( 23 ) ; earthquake in Haiti, in 2010 ( 32 ) ; disaster with the Boeing 737–800, flight IX-812, Dubai to Mangalore, in 2010 ( 34 ) . It was identified that two publications occurred after bioterrorism with Anthrax ( 25 ) disasters, one in the context of humanitarian missions ( 39 ) , six in a general context of disasters ( 36 – 38 , 42 – 44 ) and two after the September 11 attack and the occurrence of Hurricane Katrina ( 27 , 35 ) .…”
Section: Resultsmentioning
confidence: 99%
“…Humanitarian forensic action is the branch of science that involves forensic science for humanitarian purposes. It can be used to identify victims of mass disasters, or identify people who disappeared after a war, or even identify victims of epidemics (21) .…”
Section: Investigation As Part Of the Nurse's Work Processmentioning
confidence: 99%
“…This role is related to the correct filling out of documentation, communication skills with the work team, and support to the families of the population served. This function can be highlighted in times of disaster, either of human or natural origin, such as wars, floods, major accidents, and epidemics, such as Ebola and in the current pandemic of the new Coronavirus (21) .…”
Section: Investigation As Part Of the Nurse's Work Processmentioning
confidence: 99%
See 1 more Smart Citation